2020
DOI: 10.15517/psm.v17i2.40047
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados al incremento de cesáreas en México, 2011-2014

Abstract: Introducción: analizamos la prevalencia del parto vía cesárea en México para 2011-2014, buscando identificar algunos de los factores asociados a la presencia de cesárea durante el parto. Metodología: se realizó un análisis descriptivo y un modelo logístico multinivel con los registros de nacimientos del periodo 2011-2014, que incluye las características de la madre y del contexto. Resultados: se identificó que la presencia de factores relacionados con una mayor posibilidad de que el parto resulte en cesárea so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
5
0
3
Order By: Relevance
“…The results from our strati ed analysis show the complexity behind the individual-level factors associated with C-sections and nonconsented C-sections. The existing quantitative and qualitative research has shown the increased risk of C-sections for Indigenous women in Mexico (29)(30)(31). This study shows that indeed a public prenatal service location and private prenatal location are associated with non-consented C-sections in women of Indigenous belonging.…”
Section: Discussionmentioning
confidence: 57%
“…The results from our strati ed analysis show the complexity behind the individual-level factors associated with C-sections and nonconsented C-sections. The existing quantitative and qualitative research has shown the increased risk of C-sections for Indigenous women in Mexico (29)(30)(31). This study shows that indeed a public prenatal service location and private prenatal location are associated with non-consented C-sections in women of Indigenous belonging.…”
Section: Discussionmentioning
confidence: 57%
“…The results from our stratified analysis show the complexity behind the individual-level factors associated with C-sections and non-consented C-sections. The existing quantitative and qualitative research has shown the increased risk of C-sections for Indigenous women in Mexico [ 25 , 42 , 43 ]. This study shows that indeed, private prenatal service locations are associated with non-consented C-sections in women of Indigenous belonging.…”
Section: Discussionmentioning
confidence: 99%
“…Lo anterior difiere en 50 % a lo informado por Centers for Disease Control, que indicó 32.4 %. 14,16 Cabe señalar que durante la pandemia, en México los nacimientos por cesárea se incrementaron 4 %, pasaron de 46.2 % en 2019 a 50 % en 2020, 17,18 aun cuando la Organización Mundial de la Salud y autores como Betrán et al señalan que no se justifica un porcentaje de cesárea mayor a 15 %, por todas las complicaciones obstétricas asociadas. 19,20 En este estudio se observó que debido a la pandemia, en 23.3 % se interrumpió el embarazo mediante cesárea por indicación de diagnóstico de COVID-19, lo cual difiere a lo reportado por Lopes de Sousa, quien identificó un porcentaje mayor con la misma indicación (55 %).…”
Section: Discussionunclassified